The Influence of Integrated Emergency Response System (SPGDT) Health Education on Pre-Health Services on Residents' Knowledge of Maternal Emergencies in the Work Area of the Plaju Health Center - Mar’atun Ulaa; Khusnul Tisa Azmi (Jurnal Inspirasi Kesehatan, 2023)
Background: The Integrated Emergency Management System (SPGDT) is an emergency patient management system consisting of pre-hospital service elements, in-hospital and inter-hospital services. Quick response services to reduce the number of victims and avoid disability, by involving the community, competent health workers (nurses and medical personnel), emergency ambulance services and communication systems. Objective : To determine the effect of SPGDT health education on pre-health services on residents' knowledge of maternal emergencies. Methods : This research was a Quasi Experiment with a nonequivalent pretest-posttest non-control group design which was carried out in July 2023 in the working area of ​​​​the Plaju Palembang Health Center and a sample of 28 people were given health education about SPGDT in pre-health services to residents' knowledge about maternal emergencies. The media used was a booklet compiled by the researcher himself. Data analysis used the Wilcoxon test. Results: Health education statistics on prevention of pregnancy emergencies; Unsafe Abortion in Adolescents is effective in increasing respondents' knowledge with a value of 0.000. Conclusion : statistically health education is effective in increasing respondents' knowledge about SPGDT in Pre-Health Services Against Residents' Knowledge of Maternal Emergencies in the Work Area of ​​​​Plaju Palembang Health Center with a P value of 0.000. Suggestion : Suggestions for further research, namely that further research can be carried out discussing the effectiveness of health education to prevent pregnancy emergencies in pre-health services using other media.